Review on the flexural properties of fiber reinforced self compacting concrete by the addition of M-sand. (2020) - Ramesh, B.; Gokulnath, V.; Ranjithkumar, M.
Abstract: In this paper, the structure of self-compacting concretes (SCC) was made by unique exploratory frameworks. SCC has limit incorporates high deformability of security stick, more protection from the isolation between coarse and mortar when the strong courses through the restricted zone of strengthening bars. Starting late, self-compacting concrete (SCC) has expanded wide use for position in blocked strengthened strong structures with troublesome tossing conditions. For such applications, the new concrete must have high smoothness and incredible cohesiveness. In this undertaking, the experimental studies from the previous papers were done on the M20 grade SCC, arranged utilizing four unique proportions (0.3, 0.6, 0.9 and 1.2%) of polypropylene fiber and a water cement proportion of 0.45. The span of the polypropylene fiber is 5 mm. L-Box, U-Box, V-Funnel and J-Ring tests were performed to decide the properties of the new polypropylene fiber fortified concrete delivered utilizing waterway sand and production sand.